2020
DOI: 10.1080/21645515.2020.1834325
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with parents’ willingness to enroll their children in trials for COVID-19 vaccination

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has taken an unprecedented global toll and vaccination is needed to restore healthy living. Timely inclusion of children in vaccination trials is critical. We surveyed caregivers of children seeking care in 17 Emergency Departments (ED) across 6 countries during the peak of the pandemic to identify factors associated with intent to participate in COVID-19 vaccine trials. Questions about child and parent characteristics, COVID-19 expressed concerns and parental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 21 publications
3
52
4
Order By: Relevance
“…We found that higher parental educational achievement was associated with a greater intention to have a child vaccinated. This is similar to other reports on vaccination (14,41). Interestingly, this effect is independent and of greater importance than the numeracy level variable or the cognitive test score ("slow" vs. "fast" thinking), which did not emerge as signi cant predictors.…”
Section: Summary Of Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We found that higher parental educational achievement was associated with a greater intention to have a child vaccinated. This is similar to other reports on vaccination (14,41). Interestingly, this effect is independent and of greater importance than the numeracy level variable or the cognitive test score ("slow" vs. "fast" thinking), which did not emerge as signi cant predictors.…”
Section: Summary Of Resultssupporting
confidence: 90%
“…However, in this study, 19.1% of parents of children with asthma said they were "unlikely" or "very unlikely" to have their child vaccinated if a vaccine was available, and 21.0% said they were "unlikely" or "very unlikely" to get vaccinated themselves. These ndings echo growing concern about support for COVID-19 vaccination, even among parents of children with chronic diseases (40,41).…”
Section: Summary Of Resultsmentioning
confidence: 87%
“…Finally, overcoming vaccine hesitancy among women, particularly mothers, must be recognized as an urgent and vital necessity. 46 This is because women are typically the primary family healthcare consumers, 47,48 and once pediatric COVID-19 vaccines become available, mothers will control child uptake to a large extent. 49,50 * Vaccine ineligible population is the population aged 0-15 years old.…”
Section: Discussionmentioning
confidence: 99%
“…13,17,18 There was however contrary findings in the studies conducted in Jordan and an international survey where higher levels of education were not associated with willingness to uptake COVID-19 vaccine. 19,20 Perceptions of COVID-19 and its vaccine were important factors affecting willingness to uptake COVID-19 vaccine. More respondents with good perceptions were willing to take the vaccine.…”
Section: Discussionmentioning
confidence: 99%